2023
DOI: 10.1039/d2ob02308c
|View full text |Cite
|
Sign up to set email alerts
|

Visiblelight-induced ternary electron donor–acceptor complex enabled synthesis of 2-(2-hydrazinyl) thiazole derivatives and the assessment of their antioxidant and antidiabetic therapeutic potential

Abstract: A mild and eco-friendly visible-light-induced synthesis of 2-(2-Hydrazinyl) thiazole from readily accessible thiosemicarbazide, carbonyl, and phenacyl bromide in the absence of a metal catalyst and/or any extrinsic photosensitizer is reported....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 82 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…T A B L E 3 Outline for green solvent-mediated synthesis of thiazole derivatives. [77] 2 -Ethanol 80 12 h 82 [78] 3 Nanochitosan Ethanol Reflux 2.5-4.5 h 75-97 [79] 4 Sulfamic acid Water Reflux 3-6 h 64-89 [80] 5 -Ethanol Reflux 6 h 90-95 [81] 6 F e 3 O 4 @SiO 2 @KIT-6 Water RT 1-2 h 85-97 [82] 7 -PEG-600 RT 4 h 87 [83] 8 K 3 [Fe(CN) 6 ] Ethanol and KOH RT 2 h 80 [84] 9 -Water 90 20 h 65-85 [85] 10 CTAB Glycerol 40 1-3 h 82-96 [86] 11 Fe 3 O 4 @vitamin B 1 Water 80 30-45 min 79-93 [87] 12 -PEG-400 100 2-3.5 h 87-96 [88] 13 GAA PEG-300 70-75 1-1.5 h 82-96 [89] 14 -Water 135 35 min 50-89 [90] 15 Pyridine Water 150 20 h 40-84 [91] 16 -Water 60 1-6 h 65-90 [92] 17 -Glycerin RT 1-2.5 h 87-92 [93] 18 Ca/4-MePy-IL@ZY-Fe 2 O 3 and TCCA Ethanol 80 25 min 85-92 [94] 19 γ-Fe 2 O 3 @HAp@CPTMS@AT@Cu(ӀI) Ethanol RT 20-28 min 88-95 [95] 20 -Ethanol and water RT 60 min 90-98 [96] 21 Citric acid Ethanol and water Reflux 15-40 min 0-96 [97] 22 -Water Reflux 6 h 84-93 [98] 23 ZnO NP Ethanol/neat RT 2-8 min 90-99 [99] 24 PTSA PEG-400 80 2 h 79-95 [100] 25 Fe 2 O 3 NP Water RT 10-32 min 77-90 [101] 26 2-Hydroxypropyl-β-cyclodextrin Water and acetone 50 6 h 41-70 [102] 27 GAA PEG-400 70-75 1-5 h 80-95 [103] 28 Triton X-100 Water RT 5-10 min 85-98 [104] Abbreviations: CTAB, cetyl trimethyl ammonium bromide; GAA, glacial acetic acid; PEG, polyethylene glycol; PTSA, p-toluenesulfonic acid; TCCA, trichloroisocyanuric acid.…”
Section: S C H E M E 58mentioning
confidence: 99%
See 1 more Smart Citation
“…T A B L E 3 Outline for green solvent-mediated synthesis of thiazole derivatives. [77] 2 -Ethanol 80 12 h 82 [78] 3 Nanochitosan Ethanol Reflux 2.5-4.5 h 75-97 [79] 4 Sulfamic acid Water Reflux 3-6 h 64-89 [80] 5 -Ethanol Reflux 6 h 90-95 [81] 6 F e 3 O 4 @SiO 2 @KIT-6 Water RT 1-2 h 85-97 [82] 7 -PEG-600 RT 4 h 87 [83] 8 K 3 [Fe(CN) 6 ] Ethanol and KOH RT 2 h 80 [84] 9 -Water 90 20 h 65-85 [85] 10 CTAB Glycerol 40 1-3 h 82-96 [86] 11 Fe 3 O 4 @vitamin B 1 Water 80 30-45 min 79-93 [87] 12 -PEG-400 100 2-3.5 h 87-96 [88] 13 GAA PEG-300 70-75 1-1.5 h 82-96 [89] 14 -Water 135 35 min 50-89 [90] 15 Pyridine Water 150 20 h 40-84 [91] 16 -Water 60 1-6 h 65-90 [92] 17 -Glycerin RT 1-2.5 h 87-92 [93] 18 Ca/4-MePy-IL@ZY-Fe 2 O 3 and TCCA Ethanol 80 25 min 85-92 [94] 19 γ-Fe 2 O 3 @HAp@CPTMS@AT@Cu(ӀI) Ethanol RT 20-28 min 88-95 [95] 20 -Ethanol and water RT 60 min 90-98 [96] 21 Citric acid Ethanol and water Reflux 15-40 min 0-96 [97] 22 -Water Reflux 6 h 84-93 [98] 23 ZnO NP Ethanol/neat RT 2-8 min 90-99 [99] 24 PTSA PEG-400 80 2 h 79-95 [100] 25 Fe 2 O 3 NP Water RT 10-32 min 77-90 [101] 26 2-Hydroxypropyl-β-cyclodextrin Water and acetone 50 6 h 41-70 [102] 27 GAA PEG-400 70-75 1-5 h 80-95 [103] 28 Triton X-100 Water RT 5-10 min 85-98 [104] Abbreviations: CTAB, cetyl trimethyl ammonium bromide; GAA, glacial acetic acid; PEG, polyethylene glycol; PTSA, p-toluenesulfonic acid; TCCA, trichloroisocyanuric acid.…”
Section: S C H E M E 58mentioning
confidence: 99%
“…Dey et al [ 96 ] reported the reaction between thiosemicarbazide, phenacyl bromide, and acetophenone to afford 2‐(2‐hydrazinyl)thiazoles. The reactants were exposed to green light emitting diode light (9 W) in a hydroalcoholic mixture at ambient temperature for 60 min to afford an excellent yield of 90%–98% (Scheme 55).…”
Section: Green Synthetic Approach For the Synthesis Of Thiazole Deriv...mentioning
confidence: 99%
“…[36][37][38][39][40][41][42][43] The hydrazinyl thiazoles have received wide interest in organic synthesis as a result of significant biological importance. 44 The simplest synthetic approach to obtain hydrazinyl thiazole involves a one-pot reaction of aryl aldehyde, phenacyl halide, and thiosemicarbazide. The catalysts such as CuO NPs/TiO 2, 45 CH 3 COOH, 46 PEG-400, 47 [PDBMDIm]Br 48 and sulphamic acid 49 have been explored.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrazinyl thiazoles have received wide interest in organic synthesis as a result of significant biological importance 44 . The simplest synthetic approach to obtain hydrazinyl thiazole involves a one‐pot reaction of aryl aldehyde, phenacyl halide, and thiosemicarbazide.…”
Section: Introductionmentioning
confidence: 99%